Physical Exercise in the Prevention and Treatment of Colorectal Cancer: A Systematic Review - Stephanie Marie Cruz-Pierard; Samuel Olegario Iñiguez Jimenez; Fanny Cristina Guambo-Machado; Jonathan Luis Cruz-Pierard; Maybelin Samantha Iñiguez Jimenez (International Journal of Medical Toxicology and Legal Medicine, 2024)
Colorectal cancer has become a major health risk worldwide. It has been shown that increasing physical activity in patients with this pathology can improve their condition and help in their treatment. This research sought to determine what types of exercises and what effects they have in the treatment of colorectal cancer. For this, a systematic review was carried out in accordance with the PRISMA guidelines. 14 randomized controlled trials from PubMed and Web of Science between 2018 and 2023 were included that met the inclusion and exclusion criteria. In all RCTs analyzed, it was determined that aerobic physical exercise performed 3-5 times a week with moderate to vigorous intensity for at least 30 minutes showed beneficial effects in CRC by improving quality of life, survival, and reducing anxiety and depression. Evidence shows that regular exercise can reduce the risk of CRC by improving predisposing factors such as overweight and inflammation, optimizing the function of the immune system. In addition, it can be a complementary treatment including aerobic activity combined with strength. More studies are needed to standardize dosing recommendations and the specific effects of exercise in the treatment of CRC.